Public commissions on cultural and religious diversity
1 online resource (342 pages)
Keywords: In several Western countries, expert commissions composed of academics, public figures, politicians and community organisers have been established by governments or civil society to reflect on the changes and challenges of an increasingly plural society. Commission recommendations on how to ‘manage’ diversities successfully have shaped national narratives and affected law and public policies, yet research on the workings of such commissions remains rare. British Multiculturalism: From Parekh to PREVENT, and BeyondBuilding on its companion volume (Public Commissions on Cultural and Religious Diversity: Analysis, Reception and Challenges), this book engages with core concepts of identity, nationality, citizenship, freedom, equality and accommodation. It will appeal to researchers and students of public policy, sociology, anthropology, law, religion, politics, history and migration studies, as well as policymakers and anyone with a general interest in current debates on ethnic, cultural and religious diversity.Cohesive Fear: A Comment on Maclure and LacroixIntroduction. A Retrospective on Diversity Commissions: From Set-Up and Working Methods to Impacting PolicyMaking a difference: Dialogue and compromise in the Belgian Federal Round Tables of Interculturalism Religious and Cultural Diversity in Belgium: Finding the Common DenominatorRetrospective on the French Stasi CommissionThis book focuses on the experiences of expert commissions in the UK, France, Quebec and Belgium. Furthering the debate on commissions’ potential and limitations it draws on the first-hand experiences and introspection of former commission members and close observers, along with outside perspectives and critique from independent scholars.